2012
DOI: 10.1039/c2gc35197h
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids microemulsions: the key to Candida antarctica lipase B superactivity

Abstract: The activity of the commercial enzyme Candida antarctica lipase B (CaLB), in aqueous solutions of the ionic liquid 1-decyl-3-methylimidazolium chloride, [C 10 mim]Cl, at pH 7.0 was investigated. The relative enzyme activity (Act IL /Act Bf ) for ionic liquid molar concentrations ranging from 0.000-0.150 mol L −1 show an increase up to six fold in Act IL /Act Bf , with the ionic liquid molar concentration. This phenomenon is shown to be related with the formation of micelles originated by the self-aggregation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 63 publications
4
62
0
Order By: Relevance
“…Yet we could show that these micellar systems can be efficiently applied for synthesis and found enhanced reaction rates for Diels-Alder reactions compared to the rates in neat water. A similar effect was reported by Coutinho et al who found increased enzyme activity of Candida antarctica lipase B (CaLB) in aqueous solutions of the ionic liquid 1-decyl-3-methyl-imidazolium chloride, [C 10 mim]Cl [48].…”
Section: Introductionsupporting
confidence: 65%
“…Yet we could show that these micellar systems can be efficiently applied for synthesis and found enhanced reaction rates for Diels-Alder reactions compared to the rates in neat water. A similar effect was reported by Coutinho et al who found increased enzyme activity of Candida antarctica lipase B (CaLB) in aqueous solutions of the ionic liquid 1-decyl-3-methyl-imidazolium chloride, [C 10 mim]Cl [48].…”
Section: Introductionsupporting
confidence: 65%
“…Since then, a number of authors have studied the aggregation and micelle formation of ILs in aqueous solutions (24)(25)(26)(27)(28), their incorporation in mixed micelles (26)(27)(28)(29)(30)(31)(32)(33)(34) and their contribution to the modification of the physicochemical properties of surfactant micelles (24,(26)(27)(28)(29)(30)(31)(32)(33)(34). ILs with long alkyl chains were also found to be able to self-aggregate, promoting significant increments in enzymatic activity (35). The addition of ILs to a surfactant can either decrease (26,29,31) or increase (28,32,33) the CMC and also affect the aggregation number (23,24,29), depending on the ILs structural features (alkyl side chain, cation and anion) and the surfactant head group (26,29,34).…”
Section: Introductionmentioning
confidence: 99%
“…Denaturation of the enzymes poses a serious problem not only in the separation and storage of enzymes, but also in the process of biotransformation, biosensing, drug production, etc. Several strategies have been proposed so far in order to prevent denaturation of enzymes [7][11], which include chemical modification, immobilization, genetic modification and use of stabilizing agents. The addition of stabilizing agents is one of the most convenient and preferred methods for minimizing the denaturation of the enzymes [4][11].…”
Section: Introductionmentioning
confidence: 99%